The Contribution of Pesantren Education to the Internalization of Moral Values: A Case Study of Raudlatul Muta'allimin Kudus - Muhamad Zainul Umam (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2025)
This research examines the vital role of pesantren education in embedding and sustaining moral values within the broader social context, with a particular focus on Pondok Pesantren Raudlatul Muta’allimin Kudus. As traditional Islamic institutions, pesantren not only function as centers for religious instruction but also act as moral guardians that shape the character, ethics, and social behavior of students and their surrounding communities. In the midst of rapid globalization and shifting cultural dynamics, pesantren face the challenge of preserving the relevance of Islamic values while adapting to contemporary realities. The purpose of this study is to investigate how pesantren education contributes to moral development and to identify strategies utilized to instill Islamic ethics. Using a qualitative case study approach, the research gathered data through interviews, direct observation, and documentation involving kyai, teachers, students, and community members. The findings show that pesantren foster moral growth through structured daily rituals, integration of moral teachings in curriculum, exemplary leadership (uswah), and active community-based programs. These practices build discipline, honesty, empathy, and social responsibility in students, which in turn positively affect the surrounding society. Furthermore, the leadership model demonstrated by kyai and teachers plays a central role in reinforcing values through example, rather than instruction alone. The study concludes that pesantren education continues to serve as a powerful moral force by blending religious instruction with practical community engagement, ensuring that values are not only taught but also lived. This underscores the relevance of pesantren as adaptive agents of moral transformation capable of addressing the ethical challenges of modern Muslim societies. It also highlights that the pesantren framework can serve as a replicable model for strengthening character education in diverse social and cultural contexts, making it both traditional and forward-looking.